Nearshore survey and cleanup of benthic marine debris using citizen science divers along the Mediterranean coast of Israel. (1st June 2019) - Pasternak, Galia; Ribic, Christine A.; Spanier, Ehud; Ariel, Asaf; Mayzel, Boaz; Ohayon, Sarah; Zviely, Dov
Abstract: Information on marine debris along the Mediterranean coast of Israel, especially on the seafloor, is limited. Many recreational divers are enthusiasts of marine conservation and can thus contribute to data collection which does not require highly specialized training. The Society for the Protection of Nature in Israel together with The Israeli Diving Federation established the diver volunteer program "Sea Guard" ("Mishmar Hayam" in Hebrew), which supports marine conservation through citizen science. The divers were trained in marine ecology and survey methods to conduct independent surveys and lead underwater cleanups. For the first time, we have described the patterns of benthic debris density and composition in the nearshore environment of the southeastern part of the Mediterranean Sea. We found that benthic marine debris in the nearshore along the Israeli Mediterranean coast is primarily plastic, likely originating from the use of local beaches. Fishing, boating and domestic activities also play an important role as sources for marine debris. The currents' regime prevented the debris from accumulating on the seafloor in the nearshore environment, with the exception of several "debris traps". Our findings will be useful for the development of programs to improve coastal waste management. Highlights: Many recreational SCUBA divers care for the marine environment and can contribute to data collection with minimal training. Benthic marine debris data were collected from underwater cleanups organized by the Israeli Diving Federation since 2015. Citizen science underwater surveys in Israel are done by trained volunteers in framework of divers' "Sea Guard" program. Citizen science activities revealed patterns of benthic debris density and composition in the nearshore environment. Benthic marine debris along the Israeli coast is primarily plastic, likely originating from local beach recreational use.